Sediment deformation and production beneath soft-bedded Palaeozoic ice sheets - Le Heron, D. P.; Heninger, M.; Baal, C.; Bestmann, Michel (Sedimentary Geology, 2020)
The expansion of ice sheets over soft, sandy substrates was widespread in the Early Palaeozoic, during the Late Ordovician glaciation of North Africa and Arabia. Similarly, large parts of southern Africa were glaciated by soft bedded ice sheets in the Late Palaeozoic Ice Age. An unanswered question is the extent to which subglacial deformation involved the passive recycling of unconsolidated materials, or the active production of new sediment through erosion and shearing. Here, we compile thin section data dovetailed with scanning electron microscope imagery from sandy subglacial substrates from South Africa, Algeria and Libya. Six samples were collected from soft-sediment striated pavements, i.e., surfaces that were sheared and deformed subglacially in an unconsolidated state. The samples show a considerable variation in deformation style but a unifying trait is the occurrence of striated and facetted quartz sand grains. These textural features testify to grain-grain attrition, and the potential production of sediment in the subglacial environment.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Africa; Glacial; Ice Sheet; Palaeozoic; Subglacial; Tillite